Introducing the Index of Response to Stimulation (IRES): A Novel Metric for Assessing Vagus Nerve Stimulation Outcomes in Drug-Resistant Epilepsy - Flavius-Iuliu Urian; Corneliu Toader; Razvan-Adrian Covache Busuioc; Antonio-Daniel Corlatescu; Horia Petre Costin; Gabriel Iacob; Alexadru Vlad Ciurea (Medicina)
Background and Objectives: The Index of Response to Stimulation (IRES) is a new index that we introduce in this study to grade the effectiveness of vagus nerve stimulation in the treatment of drug-resistant epilepsy. We assessed 76 patients at 6, 12, and 18 months after VNS evaluating improvement with the IRES in four key dimensions: seizure duration decrease, seizure intensity decrease, improvement in quality of life, and seizure frequency decrease. This scale goes from 0, meaning no improvement, to 8, meaning maximal improvement, making the scale a really good measure of clinical utility. Materials and Methods: This retrospective study followed 76 patients aged 20–65, assessing changes in their IRES scores after VNS therapy using the ASPIRE SR 106 device. Therapy settings were adjusted biweekly to optimize efficacy and patient tolerance. Results: There were improvements in the control of the seizures, measured in terms of increased IRES scores. Improvements were associated with quality-of-life enhancements for the patient and a lesser frequency and intensity of the seizures, testifying further to the predictive ability of the IRES toward successful outcomes. This fact reveals that epilepsy treatment must be individual, according to the profile of the patient. Conclusions: The study confirms the IRES to be a valid tool for the assessment of the impact of VNS on drug-resistant epilepsy and promotes it as an integral part of the evaluation of the patient for personalized therapy. The findings encourage the use of IRES among the elements that support patient selection and insist on its role in the advancement of precision medicine and optimization of treatment.